Echocardiographic measurements of left ventricular dimensions and function in newborns with omphalocele and pulmonary - Si-Si Yang; Wen-Chang Huang; Peng Wang; Fang-Qi Gong; Tai-Xiang Liu; Jin-Fa Tou; Deng-Ming Lai (BMC, 2023)
Abstract Purpose The purpose of this study was to explore echocardiographic parameters of the left ventricle (LV) in relation to the outcomes of omphalocele neonates with pulmonary hypertension (PH). Methods This retrospective study was conducted among omphalocele patients with PH born from 2019 to 2020. Patients in this study did not have additional severe malformations or chromosomal aberrations. Patients who died under palliative care were excluded. The echocardiographic parameters of LV were obtained within 24 h after birth. Clinical and outcomes data were recorded, echocardiograms evaluated for left ventricular internal dimension in end-diastole (LVIDd), end-diastolic volume (EDV), stroke volume (SV) and cardiac output index (CI), among others. Results There were 18 omphalocele newborns with PH, of whom 14 survived and 4 died. Both groups were comparable in the baseline characteristics. Non-survival was associated with a smaller LV [LVIDd (12.2 mm versus15.7 mm, p < 0.05), EDV (3.5 ml versus 6.8 ml, p < 0.05)] and with worse systolic function [SV (2.3 ml versus 4.2 ml, p < 0.05), and CI (1.7 L/min/m2 versus 2.9 L/min/m2, p < 0.01)]. Conclusion In the cohort of omphalocele patients with PH, lower LVIDd, EDV, SV and CI were associated with mortality. Level of evidence Level III.